Effect of egg level on buffalo milk pudding - Rahman, A; Sarker, MNH; Sultana, N; Sultana, S (Asian-Australasian Journal of Food Safety and Security, 2018)
The experiment was conducted to determine the optimum level of egg in the manufacture of buffalo milk pudding. Three types of pudding were prepared using different levels of eggs (40%, 30% and 20% by weight) and a constant level of corn flour (4%) at Dairy Technology and Microbiology Laboratory of the Department of Dairy Science, Bangladesh Agricultural University, Mymensingh. Quality of pudding was evaluated by physical, chemical and microbial test. From the result of physical study (smell and taste, body and consistency, color and appearance) it was found that pudding of 40% egg obtained the best score (97.50±3.77) followed by 30% (83.96±2.52) and 20% egg containing pudding (74.93±1.01). The differences within the overall score with different level of egg had significant effect. Chemical analysis showed the significant differences (p<0.01) within the total solids (TS) (340.61±1.72, 334.18±2.10 and 327.48±2.61), moisture (659.39±1.72, 665.82±2.10 and 672.52±2.61), fat (79.37±1.90, 76.43±2.76 and 73.47±3.62), protein (60.43±0.90, 53.82±0.57 and 47.07±0.25), carbohydrate (194.02±1.07, 197.33±1.17 and 200.57±1.21) and pH (6.90±0.00, 6.93±0.21 and 6.87±0.22) but no significant differences was found in ash (6.78±0.14, 6.58±0.13 and 6.38±0.01) and acidity percentage (0.071±0.00, 0.071±0.00 and 0.071±0.00%). Microbial analysis showed that there were significant differences (p<0.01) in total bacterial count (43.00±2.65×104, 38.33±1.53×104 and 35.00±3.00×104) in the pudding containing different levels of eggs. The experiment concluded that the egg level has a significant effect on the buffalo milk. The better result for buffalo pudding is at 40% egg level by weight with 4% constant corn flour. Asian Australas. J. Food Saf. Secur. 2018, 2(1), 35-39